The Anthelmintic Effect of Pumpkin Seed (Cucurbita moschata Durch) Infusion on Lethal Death Time of Fasciola giganticaIn Vitro - Andriani Dwi Siswarini; Kusnoto Kusnoto; Retno Bijanti (Universitas Airlangga, 2017)
Fasciola gigantica is a worm which could infect breeding animal and human. One of the plants that can be used as worm drug is Pumpkin seed (Cucurbita moschata Durch).Pumpkin seed (Cucurbita moschata Durch) has been used in traditional anthelmintic medicine. This research was conducted to determine the anthelmintic effect of Pumpkin seed (Cucurbita moschata Durch) infusion on lethal death time of Fasciola gigantica in vitro. This research used Fasciola gigantica 25-75 mm in length without differentiating their sex. The concentrations of Pumpkin seed (Cucurbita moschata Durch) for treatment of Fasciola gigantica were 25%, 50% and 75%. The negative control used NaCl physiology (0.9 %). ANOVA factorial test showed significant difference among all of the experiment groups (p <0.05). Duncan multiple range test was seen the best treatment was the shortest lethal death time in concentration of 75%.Six hours of the treatment was the best time for making death of the worm. The Pumpkin seed (Cucurbita moschata Durch) in 75% dose was the best dose for making death of the worm. In 6th hours of the treatment in 75% dose administering had the best for making death of Fasciola gigantica. As for the reason, pumpkin seed (Cucurbita moschata Durch) can be use as anthelmintic.